البحث العلمي الإسلامي: أهميته في خدمة المجتمع، وآليات دمجه فيه: الأستاذ الدكتور المكي اقلاينة - Makky Klaina (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2018)
The scrutiny of the carried out researches in Islamic studies shows they focus on theoretical approach rather than practical interact with the community. Although such studies are valuable, but nobody can benefit of them apart of a closed specialized elite.This paper aims at raising awareness of the need to link Islamic studies research to the community. Its objective is to change both the methodology and topics of Islamic research. In order to achieve such a change, we have to draw plans and set smart goals taking into account the community needs. We, therefore, have to find the effective means and train the academic researchers who are able to interact with their communities